Recent advances in animal nutrition in Malaysia: its relevance and importance for farming system in Indonesia - Mohd Jelan, Zainal Aznam (Pusat Penelitian dan Pengembangan Peternakan, 2005)
Malaysia aims to improve its livestock industry particularly in ruminants production by increasing its farm output so that she could reduce the importation of goat meat, beef and milk. Improving the ruminant production is also a security strategy to ensure a significant availability of protein food to its increasing population. Currently, Malaysia is a net importer of these farm products and the trend will increase due to a higher demand of the increasing population who has a greater intake for red meat and milk. To improve the production of these products, the animal population base also has to increase. The cost of animal production is strongly associated with the cost of feeding. As such, matching the rearing system with the feed resources and the feeding system are important part of the production system. Using local resources has been our strategy, as is also being done in Indonesia. However, it is important that the resources are used to the maximum for the best benefit. The tropical climate is suitable for the production of many tree forages that are rich in protein. These are leguminous or non-leguminous forages that are being encouraged to be grown by smallholders. Agricultural residues are abundant and are widely used in Malaysia. Even though the fibrous materials such as the rice straw are poorly utilized, the by-products from the oil palm industry is important and contribute significantly to the feeding system for ruminants. These include the use of forages under the oil palm plantations and utilization of energy and protein rich by-products such as palm kernel cake in formulated feed. There are also growing interest to commercially grow other forages such as alfalfa and kenaf. It is hope that the feeding system utilized the available resources and the cost of feeding is kept cheapest possible. Research and development programmes are underway to ensure maximum incorporation of local resources in the diet by improving the nutritive values of the feeds.